THE EFFECTIVENESS OF DENTAL HEALTH COUNSELING ONLINE IN IMPROVING KNOWLEDGE OF HOW TO MAINTENANCE DENTAL HEALTH IN GIANYAR TOURISM COMMUNITY MEMBERS IN 2020 - I Gede Surya Kencana; I Nyoman Gejir; I Made Budi Artawa; Regina Tedjasulaksana; Anak Agung Gede Agung (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
Health promotion is one of the efforts to improve the capacity of the community, through learning from, by, for and with the community. Thus they can help themselves, and develop community-based activities, in accordance with the culture of the local community and are supported by policies with a health perspective. The purpose of this study was to determine the effectiveness of online dental and oral health education in increasing knowledge about dental and oral health care for members of the Gianyar tourism community. This research is a pre-experimental study with one group pre and post test design. The number of respondents in this study were 80 people consisting of 47 men (58.75%) and 33 women (41.25%). The education level of respondents was mostly high school / equivalent 27 people (33.75%) and at least 2 people (2.5%) at postgraduate level. The average level of knowledge of respondents before being given counseling on oral health was 66.18 and after counseling was 74.18. The results of the Wilcoxon Signed Rank Test statistical test obtained a negative ranks value of 0, which means there is no decrease from the pertest value to the post-test value. The positive rank value was 77, this result shows that 77 respondents experienced an increase in the value from the pretest to posttest. The conclusion of this study is that respondents have increased their knowledge after being given counseling on dental health maintenance.